Development of Game-Based Karate Basic Technique Activities at Dojo Parulian 2 Medan - Mahmuddin; Riza, Ade Ros; Ishak, Muhammad; Silwan, Argubi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
This study aims to develop game-based karate movement activities that can increase the effectiveness of training and active participation of Dojo Parulian 2 Medan members categorized as elementary schools aged 6 to 12 years. This research uses the Research and Development (R&D) research method developed by Sugiyono. With eight stages, namely potential and problems, collecting data, product design, design validation, design revision, product trial, product revision, trial use. This research was conducted at dojo Parulian 2 Medan with a small scale trial of 10 people and a large scale trial of 15 people. Based on the results of data analysis, it shows that the product quality assessment